2017
DOI: 10.3892/ol.2017.6907
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of EGFR mutation and factors associated with clinical tumor stage at diagnosis: Experience of the INSIGHT study in Poland

Abstract: Abstract. Targeted therapy of non-small cell lung cancer (NSCLC) patients with mutations in the epidermal growth factor receptor (EGFR) gene has been associated with improved prognosis. However, there is a shortage on data from real-world clinical practice in management of EGFR-positive NSCLC patients in Poland. The present study retrospectively analyzed data from the INSIGHT study to evaluate the incidence and clinical management of EGFR-positive NSCLC in Poland. The authors additionally aimed to identify pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 43 publications
(55 reference statements)
2
7
0
Order By: Relevance
“…Of the patients at IPO-Porto with NSQ who were tested for EGFR or ALK mutations/rearrangements, 20.1 and 8.8%, respectively, were found to have mutations/rearrangements. These rates are comparable to those reported in several observational studies conducted in Portugal and elsewhere in Europe in which rates ranged from 10 to 28% for EGFR mutations [15][16][17][18][23][24][25][26][27], and from 3 to 12% for ALK rearrangements [17,24].…”
Section: Discussionsupporting
confidence: 87%
“…Of the patients at IPO-Porto with NSQ who were tested for EGFR or ALK mutations/rearrangements, 20.1 and 8.8%, respectively, were found to have mutations/rearrangements. These rates are comparable to those reported in several observational studies conducted in Portugal and elsewhere in Europe in which rates ranged from 10 to 28% for EGFR mutations [15][16][17][18][23][24][25][26][27], and from 3 to 12% for ALK rearrangements [17,24].…”
Section: Discussionsupporting
confidence: 87%
“…EGFR exon 19 deletion and L858R mutation were more commonly observed in female patients and adenocarcinoma. Similar observation has been reported between L858R mutation and gender, smoking, and histological type in a Japanese cohort [23] and a Polish cohort [24]. Further subgroup analysis confirmed the increased prevalence of those genetic variations in female patients in adenocarcinoma subgroup, and also in adenocarcinoma in male patients, which was not performed in previous studies.…”
Section: Plos Onesupporting
confidence: 88%
“…Interestingly, after further standardization of smoking status, we found that in non-smokers, male patients were more likely to have squamous cell carcinoma and KRAS mutations and less likely to have EGFR L858R mutation than female patients. Previous study by Xue et al [26] and Ramlau et al [24] found that KRAS mutation was more common in male patients in a Chinese cohort, and EGFR L858R mutation was more common in female patients in the Polish cohort, but further standardization of smoking status was not performed in the study. Study by Stapelfeld et al [27] reported conflicting results that KRAS mutations were more frequently found in women than in men, possibly due to the different race of patients (Caucasian) investigated in that study.…”
Section: Plos Onementioning
confidence: 88%
“…Positive expression of EGFR is correlated with poor prognosis in several tumors, including TNBC [24,25]. EGFR overexpression has been detected in TNBC cell lines such as MDA-MB-231, BT-20, and HCC1937 [26].…”
Section: Discussionmentioning
confidence: 99%
“…Cell viability at different time points (24,48, 72 and 96 h) was evaluated by 3-(4, 5-dimethyl-2-thiazolyl)-2, 5-diphenyl-2H-tetrazolium bromide (MTT) colorimetric assay. Briefly, 20 μl MTT solution (5 mg/mL; SigmaAldrich, St. Louis, Mo, USA) was added into each well, and cells were incubated at 37 °C for another 4 h. The reaction was terminated with 150 μL of dimethylsulfoxide (DMSO, Sigma-Aldrich) per well.…”
Section: Cell Culture and Transfectionmentioning
confidence: 99%